Use of Nutrition Assessment of Cancer Patients with Chemotherapy: Literature Review - Irawati Irawati; Tahir Tahir; Kadek Ayu Erika (Indonesian Journal of Global Health Research, 2021)
Along with the increasing number of cases diagnosed with cancer, cancer treatment therapy is growing, one of which is chemotherapy. Chemotherapy is an indicated treatment for systemic, metastatic, and advanced cancers, whose use has increased from one to four in 10 patients diagnosed with cancer. This is because chemotherapy can reduce recurrence rates and prolong life. However, chemotherapy has some serious side effects, such as experiencing nutritional problems during and after chemotherapy, even continuing for the next year. Thus, the need for early screening to detect patients at risk for nutritional problems. The purpose of this study was to determine the use of appropriate nutritional assessment in cancer patients with chemotherapy. This research study is a literature review using PI(E)O (patient, intervention/exposure and outcome) to determine the keywords used in searches in several databases. The databases used are PubMed, Wiley Online Library, Science Director and Google Scholar. The keywords used are (Cancer AND Chemotherapy) AND (Assessment OR Measurement OR Instrument OR Screening) AND (Nutrition OR Nutritional Status OR Nutrition Score). A total of articles 134,274 were identified, after being screened for the last 5 years (2016-2021), in English, full text, duplication, and according to the title and abstract, obtained 73 articles and nine article include this study. The results of a literature search found nine articles describing nutritional assessments used by cancer patients with chemotherapy, namely; PG-SGA as many as four articles, NRS-2002 as many as two articles, MST as many as one article, MNA as many as one article, and a combination of MUST and PG-SGA as many as one article. PG-SGA is a nutritional assessment that is precise, effective, easy, accurate, simple, and has high sensitivity. In addition, PG-SGA can be used in conjunction with other nutritional assessments, and is proven to be efficient.